David Godschalk: A Planner's Lifelong Search for the Sweet Spot. Issue 1 (2nd January 2019) - Berke, Philip R.; Rodriguez, Daniel A.
Abstract: David R. Godschalk, professor emeritus in the Department of City and Regional Planning at the University of North Carolina, Chapel Hill, passed away in early 2018. In this essay we reflect on Dave's planning scholarship and practice. We discuss his main contributions in 4 prominent areas. First is the importance of public participation and collaboration for the planning and governance of communities. He argued for democratizing and recasting public participation, with planners working alongside community members coproducing plans and incorporating uncertainty, new information, and different viewpoints. Second is Dave's focus on the tenets of the comprehensive plan and its core element, the land use plan. In the plan, central principles of livable urban forms and model planning processes can be integrated and translated to practice. With academic collaborators and practitioners he pioneered theoretical and empirical research on what constitutes a high-quality plan, a fundamental question at the heart of planning. Third is his research demonstrating how spatial planning can be used for hazard mitigation and urban resilience. This work forged a new generation of planning academics and practitioners who focused on hazard plans for predisaster mitigation and postdisaster recovery at multiple governmental levels. Finally, fourth is his personal involvement in planning-related institutions that he helped create, lead, or steer. In his various roles as scholar, teacher, mentor, collaborator, supervisor, planning director, and elected official, Dave touched the lives of many who now build on his contributions in creating better communities.